Wizerunek pustyni i jej mieszkańców w świetle świadectw Świętych Ojców z Synaju - Wolińska, Teresa (Vox Patrum, 2018)
We owe important testimonies about local nomads to monks and pilgrims visiting Sinai. The information about them can be found in the works of Nilus of Sinai, Nilus of Ancyra, Ammonius, Jerome, Anastasius Sinaita or John Moschos. The image of the nomads, both Arabs and Blemmyds is painted in rather dark colours. The Christian authors pointed to the fact that they did not have permanent residences, nor cultivated land, but lived on what they hunted or robbed. They devoted much attention to the attacks of the nomads on monasteries, hermits and pilgrims. They also reported the fate of the latter in captivity. They were shocked by Saracen beliefs, the cult of al-Uzza, identified with Aphrodite and bloody victims, especially human, although the latter has often been questioned by researchers. It seems that such practices may have happened, although rarely. Those Saracens who had adopted Christianity were presented in a different manner. They were allies of monks and hermits, defending them fromtheir pagan brothers. Even if their customs had not radically changed, for the Christian writers they were no longer barbarians. In the written sources, there is little information about collaboration between ascetics and nomadic communities, although we know from the archaeological sources that it took place, even in the form of trade exchange.